Cord formation in Mycobacterium abscessus - C Adikaram; J Perera; GMM Perera (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2015)
A sputum sample was received from a young woman with a past history of pulmonary mycobacterial disease (< 6 months). She has treated 6 month with first line anti tuberculosis drugs based on clinical symptoms and AFB microscopy (AFB positive) and she has cured. Next time, she came with cough and mild fever again. Molecular based laboratory identification of the sputum specimen confirmed that she has Mycobacterium abscessus infection. After treating with sodium hydroxide (4%) (Sigma), it was centrifuged at 3000 g under refrigerated conditions (at 4°C). The centrifuged deposit was diluted in 1 ml of sterile distilled water to prepare the bacterial suspension. Two slopes of the Lowenstein-Jensen (L-J) medium (Difco), one containing paranitrobenzoic acid (PNB, Sigma) and 7H9 broth medium were inoculated with 100 μl of the bacterial suspension. A small portion of the bacterial suspension (~20 μl) was examined microscopically, using the Ziehl-Neelsen (ZN) stain, to determine the presence of acid fast bacilli (AFB). The inoculated media were incubated at 37°C in a 5% CO2 incubator. The phenotypic characters of colonies were observed and smears were prepared from cultures grown on all 3 media. Culture isolates were tested by nitrate reductase test.